2013
DOI: 10.1111/crj.12056
|View full text |Cite
|
Sign up to set email alerts
|

Influenza pneumonia among adolescents and adults: a concurrent comparison between influenza A (H1N1) pdm09 and A (H3N2) in the post‐pandemic period

Abstract: IntroductionComparisons of the characteristics between the influenza A (H1N1) pdm09 and common seasonal influenza are important for both clinical management and epidemiological studies. However, the differences between pandemic and seasonal influenza during the post-pandemic period are poorly understood.ObjectivesThe aim of our research was to investigate clinical and immune response differences between patients with influenza A (H1N1) pdm09 pneumonia and seasonal influenza A (H3N2) pneumonia in the post-pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 22 publications
1
14
0
2
Order By: Relevance
“…An overview of the studies (Table and Table ) showed a lot of diversity in the populations that were investigated: Studies are presented in terms of hospitalized patients (n = 22) or cover mainly outpatient settings (n = 19), such as primary care (n = 6) or community‐based (n = 4) settings. Most studies were carried out in Asia (n = 17), Europe (n = 15), or North America (n = 8).…”
Section: Resultsmentioning
confidence: 99%
“…An overview of the studies (Table and Table ) showed a lot of diversity in the populations that were investigated: Studies are presented in terms of hospitalized patients (n = 22) or cover mainly outpatient settings (n = 19), such as primary care (n = 6) or community‐based (n = 4) settings. Most studies were carried out in Asia (n = 17), Europe (n = 15), or North America (n = 8).…”
Section: Resultsmentioning
confidence: 99%
“…The present results are in agreement with another group that reported that IL-10 was found to be higher in influenza A (H1N1)pdm09 patients when compared with other influenza A viruses. However, other influenza viruses in the group of non-(H1N1)pdm09 pneumonia patients were not tested (42,43). IL-17 has been associated with acute lung injury in influenza A (H1N1)pdm09 patients (24).…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids were widely used in patients with severe influenza infection. The use of corticosteroids is based on the underlying pathogenesis of severe influenza infection, which is characterized by overproduction of proinflammatory cytokines/chemokines and an excess of activated lymphocytes, which may result in severe lung damage and delayed recovery . Moreover, animal model studies also found that corticosteroid treatment decreased mortality and ameliorated the acute lung injury induced by influenza A(H1N1)pdm09 virus .…”
Section: Introductionmentioning
confidence: 99%